Pengaruh Konsumsi Rumput Laut (Eucheuma Sp) terhadap Peningkatan Kadar Hemoglobin dan Status Fe Ibu Hamil Anemia di Kabupaten Pekalongan - Uluwiyatun Uluwiyatun; Runjati Runjati; Ari Suwondo (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2014)
Anemia in pregnancy is a condition in pregnant women with hemoglobin levels less than 10.5 g% in the second trimester . Prevention of anemia during pregnancy is done by administering tablets Fe for 90 days at a dose of 60 mg . Each tablet contains 320 mg of FeSO4 (iron 60 mg ) and 500 mg of folic acid . Pregnant women besides taking iron tablets, needs to be supported with nutritional patterns which contain some necessary intermediate in the synthesis of hemoglobin . Seaweed ( Eucheuma sp ) is one of the few foods that contain the necessary intermediate in the synthesis of hemoglobin such as iron , protein danvitamin B complex . Objective To analyze the effect of the consumption of seaweed ( Eucheuma sp ) to increased levels of hemoglobin and anemia maternal Fe status. Research Method T-test dependent and independent T -test . Hb measurements using measuring instruments and measurement Hemoque Fe status indicators TIBC Ferritin using measuring instruments . Results The study was conducted on 30 respondents consisting of a control group ( tablets Fe ) and the experimental group ( Seaweeds and tablets Fe ) . Average hemoglobin levels in pregnant women who consume seaweed when the pretest was 9.373 g / dl , mean Hb level when post-test was 10.847 grams / dl . Average iron status in pregnant women who consume seaweed when the pretest was 14.238 ng / ml , the average Fe status when the posttest was 25.530 ng / ml . The results of the independent t- test found no effect of the consumption of seaweed ( Eucheuma sp ) to increased levels of Hb with ρ value of 0.004 . Results of Mann-Whitney test found no effect of the consumption of seaweed ( Eucheuma sp ) to the increase in iron status . Conclusion The provision of seaweed jelly mempegaruhi significantly elevated levels of Hb and no effect on the improvement of iron status .